Rare sighting of a right whale ( Eubalaena glacialis ) in Hawaii - Rowntree, V.; Darling, J.; Silber, G.; Ferrari, M. (Canadian Journal of Zoology, 1980)
The presence of a right whale (Eubalaena glacialis) in the Hawaiian waters on March 25, 1979 was documented by photographs which allow individual recognition. The sighting is significant because right whales have not been reported in these waters since 1851 and because the North Pacific population has been estimated to number only 100–200 individuals even though the killing of right whales has been banned since 1937.